Th17 cells: a promising therapeutic target for Parkinson's disease? - Prots, Iryna; Winner, Beate (Expert Opinion on Therapeutic Targets, 2019)
Introduction: Parkinson's disease (PD) is the most common neurodegenerative movement disorder caused by the progressive loss of neurons in the midbrain and other brain regions. Only symptomatic treatment is currently available. Mounting evidence suggests that T cells are a key contributor to PD pathogenesis and neurodegeneration by a mechanism that requires further elucidation. Areas covered: We discuss the evidence of imbalanced activation of effector T cell populations in PD and summarize the data of Th17 involvement and Th17-regulated mechanisms in PD pathology. Moreover, possible Th17-related molecular targets as possible neuroprotective immunomodulatory therapeutic targets for PD are examined. Expert Opinion: Existing data show that Th17 cells, their effector molecules, and signaling pathways are potentially effective therapeutic targets for neuroprotective immunomodulation in PD treatment. However, specificity of action within Th17-mediated signaling pathways for PD requires careful consideration.
CRIS-Team WoS Importer:2019-04-09
Keywords: T cells; Th17 cells; neurodegeneration; Parkinson’s disease; IL-6; IL-1β